Dampak Dampak Supervisi Terhadap Peningkatkan Kurikulum Sekolah Pada Yayasan Pendidikan Al-Ihsan Medan Tembung - Leni Hermita Hasibuan; Eliza Putri; Tria Indah Ristika; Eka Putri Wildiyani; Sri Andriani (El-Idare, 2022)
Supervision is a supervision carried out by superiors to subordinates, such as school principals against teachers. Supervision makes teachers more careful about their teaching materials and of course can determine the best teaching methods so that educators can understand them. Supervision can also be said as a curriculum with guidance in the form of guidance which is expected to improve curriculum in the teaching and learning process. And in this study, we will discuss the impact of supervision on improving the school curriculum which is carried out at the Al-Ihsan Education Foundation, Medan Tembung. To improve the curriculum, supervision must be carried out properly and of course the guidance carried out can give positive results.